Unraveling consistently altered brain activations of language deficits in schizophrenia: evidence from ALE meta-analysis - Yuwen He; Ya Hou; Yuan Zhou; Ruolei Gu; Fei Gao; Zhen Yuan (Translational Psychiatry)
Abstract Background Language deficits are commonly observed in patients with schizophrenia, significantly impacting their quality of life. Current medicine has little curing effects on language deficits in patients with schizophrenia. Therefore, it is crucial to investigate the underlying pathology of these deficits and unravel the potential intervention targets. Methods We systematically reviewed fMRI publications on language processing in schizophrenia and summarized the evidence quantitatively with activation likelihood estimation algorithms following PRISMA guidelines. A total of 82 experiments involving 1538 schizophrenia patients and 1413 healthy controls were included in the current study. Results Our findings revealed that the left middle frontal gyrus (MFG) and inferior frontal gyrus (IFG) were consistently related to language deficits in schizophrenia across all modalities and all contrasts. Subsequent analysis revealed increased activation in the left MFG related to language deficits in schizophrenia. Subgroup analyses uncovered modality-specific alterations. Specifically, reduced activation in bilateral MFG in language comprehension, and increased activation in left IFG in language production in schizophrenia. Further evidence in comparison analysis also uncovered greater alteration in right MFG related to comprehension than production, while greater alterations in left IFG and others related to production than comprehension in schizophrenia. Moreover, we found that age modulates the altered activation patterns in schizophrenia, while positive or negative symptoms, or sex, did not show significant correlations with these patterns. Conclusions In summary, our study highlights convergent altered activation patterns in specific brain regions and identifies several heterogeneous sources (e.g., language modality, age) contributing to language deficits in schizophrenia.